2014
DOI: 10.1520/mpc20130110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of External Factors on the Cooling Ability of Vacuum Quenching Oils

Abstract: This paper presents research on vacuum quenching oils at different pressure conditions during the cooling stage of the heat treatment process. The aim of this work is to reveal the influence of the pressure, agitation (laminar or turbulent flow), and oil temperature on the cooling oil. Medium and low viscosity oils are investigated. The research is novel because it expands knowledge of quenching oil behavior at low and high pressure conditions (from 1 mbar to 2.5·103 mbars). The findings are presented as integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The cooling process primarily consists of three stages: film boiling, nucleate boiling, and convective heat transfer [10]. Gospodinov et al [11] demonstrated that the cooling ability of vacuum quenching oil is affected by the chamber pressure, agitation, and oil temperature. However, Troell et al [12] reported that the cooling characteristic does not significantly vary for the given pressure (0.4–1.4 bar) above the oil tank, and decreased quenching distortion is only observed at a higher pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The cooling process primarily consists of three stages: film boiling, nucleate boiling, and convective heat transfer [10]. Gospodinov et al [11] demonstrated that the cooling ability of vacuum quenching oil is affected by the chamber pressure, agitation, and oil temperature. However, Troell et al [12] reported that the cooling characteristic does not significantly vary for the given pressure (0.4–1.4 bar) above the oil tank, and decreased quenching distortion is only observed at a higher pressure.…”
Section: Introductionmentioning
confidence: 99%